(untitled) (Journal of Academic Research, 2025)
This study aims to investigate the relationship between exam anxiety and academic achievement among the students of the Faculty of Arts in Misurata. The research population consisted of all students who enrolled in Education and Community Problems Course at the Department of Education, Fall 2022- 2023. They were 34 students and as a result of the population small size, the study applied the research tool on the entire study sample. Furthermore, to accomplish the aim of the study, the researcher employed Chales Spellerler Scale which was utilized by the researcher; Zainab Al-Ghawil in her study of the Libyan environment during the academic year 2007. The results of the current study indicated that there was a negative correlation between exam anxiety and academic achievement because the correlation coefficient value was (0.22-0.22). As the correlation coefficient is negative, this indicates that the type of correlation between anxiety and academic achievement was inverse correlation and the size of correlation is weak and non-significant at the level (0.05). Based on this result, it is explicit that the correlation relationship between exam anxiety and academic achievement is logical. Thus when the exam anxiety level is high, academic achievement level is low and when the exam anxiety level is low, the level of academic achievement is high. Based on these results, the researcher came up with some recommendations that were: conducting university exams in conditions which take into account the psychological state of the student; such as setting exam dates on prior dates known to the student, setting a suitable exam schedule based on exam difficulty, and taking into account the time required for exam preparation. Also, reconsidering the process of evaluating university student, and not focusing on the results of paper exams as a means of granting the student a certificate.